Exploring the Discursive Function of Hashtags: A Semantic Network Analysis of JUUL-Related Instagram Messages. (October 2021) - Kostygina, Ganna; Feng, Miao; Czaplicki, Lauren; Tran, Hy; Tulsiani, Shreya; Perks, Siobhan N.; Emery, Sherry; Schillo, Barbara
This study used semantic network analysis to investigate the themes of JUUL electronic cigarette-related messages on Instagram posted by three account types (commercial, vape community, and organic users) and explore the function of hashtags in the JUUL-related discourse across these groups. Posts were collected from 1 March 2018 to 15 May 2018. We conducted network analyses for each user group, with separate analyses to examine texts with and without inclusion of hashtags. Network statistics determined which words occurred most frequently, which words co-occurred or clustered together, and what communication function hashtags perform. Analyses of message content with hashtags included revealed that the largest cluster of terms by account type was brand promotion (commercial), brand engagement (community), and youth social use of JUUL and other substances, such as marijuana (organic users). On removal of hashtags, the largest cluster for each group was online and offline retailer promotion (commercial), JUUL promotion or shares of existing promotional content (community), and youth social use (organic users). Commercial accounts used hashtags to increase brand visibility and engage with vape communities present on Instagram. Community accounts served as discursive intermediaries between commercial accounts and organic users, fostering organic user engagement with brands. Social media serve as an extension of real-life peer groups among youth and young adults. Community accounts, which likely have greater credibility among users compared to commercial accounts, may help enhance the effects of targeted promotion and normalize vaping comprehensive regulation of commercial digital tobacco marketing is necessary to reduce the amount of commercial content youth and other consumers are exposed to through overt commercial and influential community accounts.